2016
DOI: 10.1016/j.ijotn.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of orthopaedic and trauma nurses who have cared for adults with a learning disability

Abstract: There was evidence of good practices within orthopaedic and trauma settings such as the active involvement of family or a paid carer who is known to thepatient and the modification of care and interventions along with specialist advice and support from the Acute Liaison Learning Disability Nurse. There were areas of concern such as the lack of use of Hospital Passports and the inconsistent implementation of reasonable and achievable adjustments. It is unknown if the care for patients with a learning disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…All hospitals in the UK have a legal responsibility to provide reasonable adjustments for people with an intellectual disability (Equality Act, 2010) and this encompasses changes to communication methods, provision of easier to read information, use of hospital/communication passports and reasonably adjusted procedures (Drozd and Clinch, 2016), for example the completion of PROMS questionnaires that are tailored to meet the individual needs of patients with intellectual disabilities, communication difficulties and/or cognitive impairments. Good health care services are individualised and person-centred with a focus on the quality of the relationship with staff and the person with an intellectual disability (Mansell, 2010) which is the same requirement as for a patient without an intellectual disability, communication difficulty or cognitive impairment.…”
Section: The Problems and Pitfalls Of Using Proms In Clinical Assessmentmentioning
confidence: 99%
“…All hospitals in the UK have a legal responsibility to provide reasonable adjustments for people with an intellectual disability (Equality Act, 2010) and this encompasses changes to communication methods, provision of easier to read information, use of hospital/communication passports and reasonably adjusted procedures (Drozd and Clinch, 2016), for example the completion of PROMS questionnaires that are tailored to meet the individual needs of patients with intellectual disabilities, communication difficulties and/or cognitive impairments. Good health care services are individualised and person-centred with a focus on the quality of the relationship with staff and the person with an intellectual disability (Mansell, 2010) which is the same requirement as for a patient without an intellectual disability, communication difficulty or cognitive impairment.…”
Section: The Problems and Pitfalls Of Using Proms In Clinical Assessmentmentioning
confidence: 99%
“…Whilst research in this area is limited, similar findings have, however, been reported elsewhere. Drozd and Clinch () undertook a survey with a convenience sample of 13 nurses attending an international trauma and orthopaedic nursing conference and found that only two (15%) had seen a hospital passport used to support people with intellectual disabilities in orthopaedic or trauma settings. This study only surveyed a small sample (and cannot therefore be generalised); nonetheless, it does give rise to concerns given that admissions to such clinical settings are likely to occur as an emergency, that treatment is likely to be required quickly and that communication may be a particular challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Drozd and Clinch () argue that further research is needed to determine why hospital passports are not being used as intended by healthcare staff to support the care of people with intellectual disabilities in hospital settings. The factors contributing to this situation are likely to be complex and relate to both the content of such documents (Tuffrey‐Wijne et al., ) and organisational issues (Bell, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations